A Multimethod, Case-Controlled Study of Sleep–Wake Disturbances in Adolescents With Spina Bifida. (20th December 2017) - Murray, Caitlin B; Palermo, Tonya M; Holmbeck, Grayson N
Abstract: Objective: This study aimed to compare sleep–wake disturbances in adolescents with spina bifida (SB) to typically developing (TD) peers. Exploratory analyses examined sex as moderator of disrupted sleep. Methods: Adolescents with SB (ages 12–18 years; N  = 37) and a demographically matched sample of TD adolescents ( N  = 37) completed validated sleep questionnaires and underwent 10 days of actigraphy monitoring. Results: Adolescents with SB evidenced worse sleep quality, shorter sleep duration, greater sleep maintenance difficulties, and higher levels of fatigue compared with their TD peers. Exploratory analyses revealed females with SB were particularly vulnerable to developing sleep disturbances. Conclusions: Adolescents with SB are at risk for nighttime sleep disturbances and daytime fatigue. Additional research will need to identify mechanisms and adverse consequences of poor sleep to develop interventions addressing sleep deficiency. Sex-specific disparities in sleep patterns in pediatric SB is a novel finding that requires assessment of etiological underpinnings to clarify clinical implications.